Mechanical property study of plywood bonded with dimethylol dihydroxy ethylene urea crosslinked rice starch- natural rubber latex-based adhesive - Soubam, Triveni; Gupta, Arun Kumar; Sharma, Swati; Saidatul Shima, Jamari (Elsevier Ltd, 2022)
There has been an increase in the demand for adhesives due to the increasing applications of plywood panels in the home furnishings and decorative items industries around the world. Most of the wood-based panels industry depends on synthetic adhesives due to its low cost and high performance. However, because synthetic adhesives emit the carcinogenic gas formaldehyde and increase the risk of human health, there is a growing interest in developing non-toxic and eco-friendly wood adhesives made from renewable materials. The present research aims to develop a bio-adhesive for plywood bonding based on two biopolymers: natural rubber latex (NRL) and dimethylol dihydroxy ethylene urea (DMDHEU) crosslinked rice starch. A bio-adhesive was ultimately formulated with varying weight ratio of NRL and DMDHEU crosslinked rice starch at 1:3, 1:1 and 3:1 respectively. Mechanical characteristics of plywood samples fabricated with the formulated bio-adhesive were measured using IS 17,304 and ISO 12466–1-2007 via hot press at 120 °C. The modulus of rupture (MOR) of plywood glued with Dm-B was 63 MPa, the modulus of elasticity (MOE) was 6480 MPa, and the internal bonding (IB) was 1.48 MPa, each of which met the ISO 12466–2-2007 and IS 303 standards. According to the findings, Dm-B had a profound impact on the performance of adhesion properties and contributed to the elimination of the use of hazardous synthetic adhesives.